Religious Diversity and its Legal Problems - Husni Husni; Zulfan Zulfan; Teuku Yudi Afrizal; Nurarafah Nurarafah; Sumiadi Sumiadi (Publikasi Indonesia, 2022)
The basis for freedom of religion in Indonesia is regulated in Article 28E, Article 28I, Article 29 of the 1945 Constitution and Article 4, Article 22 of Law Number 39 of 1999 concerning Human Rights. However, this freedom is not absolute and must be limited to maintain religious harmony in Indonesia. This study aims to determine the actions that often trigger religious disputes with blasphemy or blasphemy of religion either directly or through various online media. This type of research is doctrinal or normative. In this study, all norms, legal principles, legal documents, court decisions, laws and regulations related to religious freedom in Indonesia will be studied. Based on the results of research to maintain religious harmony, the government issued Law Number 1 of 1946 concerning the Criminal Code, Law Number 1/PNPS/1965 concerning the Prevention of Abuse and/or Blasphemy of Religion, Law Number 40 of 2008 concerning the Elimination of Race and Religious Blasphemy. Religion. Ethnic Discrimination, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Transaction Information. In addition to legal action against perpetrators of blasphemy, the government and the community must work together to maintain religious tolerance and prevent fanaticism towards their respective religious identities so that it has the potential to cause horizontal conflicts between religious adherents in Indonesia.